Long-term Behavior Change Through Yoga and Meditation Among Secondary School Children: Review of Buddhism - Ghimire, Mayanath; Mishra, Shila; Mahatara, Manraj (GS WOW: Wisdom of Worthy Research Journal, 2025)
To examine the effectiveness of Buddhist ideology in promoting long-term behavioural changes in school children through yoga and meditation. This study utilized the scientific review process as a Meta synthesis to determine the effectiveness of Buddhism Ideology in facilitating long-term learning behaviour changes through yoga and meditation among school-level children in Nepal, framed within a pragmatic research philosophy. Extensive archival analysis followed by a thorough review would be the strategies employed during the scientific review. Based on the nature of data availability, both qualitative and quantitative research approaches would prove effective. The review was systematically executed through the gathering of research articles alongside reports and data. Bhagavadgita, known as Yoga Sastra, is a seminal text on Yoga. Yoga has been a fundamental element of human efforts directed towards achieving higher spiritual achievements. The importance of meditation practice for students is emphasized, and it also recommends teaching all students meditation and yoga to improve academic performance. Programs centered around yoga for middle school students showed benefits in mental health, executive functioning, and physical, social, and academic aspects for learners. It is a method and asset that can be incorporated into the daily lives of students to improve academic performance and lower stress levels.